5, 6‐Bis(octyloxy)benzo[c][1, 2, 5]thiadiazole‐Bridged Dyes for Dye‐Sensitized Solar Cells with High Open‐Circuit Voltage Performance. Issue 9 (7th February 2013) - Chen, Long; Li, Xin; Ying, Weijiang; Zhang, Xiaoyu; Guo, Fuling; Li, Jing; Hua, Jianli
Abstract: Three new metal‐free dyes with a 5, 6‐bis(octyloxy)benzo[ c ][1, 2, 5]thiadiazole core (DOBT‐I–III ) have been designed and synthesized for use as DSSCs. Their absorption properties and electrochemical and photovoltaic performances have been investigated systematically. The DSSCs based onDOBT‐I–III show high open‐circuit voltages ( V oc ) of 829, 818, and 784 mV, respectively. Of the three dyes, DOBT‐III, which contains a thiophene‐bridging linker, exhibits the best photovoltaic performance: a short‐circuit photocurrent density ( J sc ) of 12.74 mA cm –2 and a fill factor ( FF ) of 0.73, which corresponds to an overall conversion efficiency of 7.29 % under standard global AM 1.5 solar conditions. Abstract : Three new dyes with a 5, 6‐bis(octyloxy)benzo[ c ][1, 2, 5]thiadiazole core (DOBT‐I–III ) have been designed and synthesized for use as dye‐sensitized solar cells (DSSCs).DOBT‐I–III show high open‐circuit voltages (0.78–0.83 V) with the DSSCs based onDOBT‐III, which contains a thiophene‐bridging linker, exhibiting the best photovoltaic performance with a power conversion efficiency of up to 7.29 %.